ETHNOMATHEMATIC EXPLORATION: DECORATIVE VARIETIES OF METHODOLOGICAL DELICATIONS - Muthia Hanifah; Tanti Jumaisyaroh Siregar (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2024)
Ethnomathematics is a mathematical science that continues to grow and develop, because cultural influences make learning mathematics no longer boring. Ethnomathematics has become a trend in the field of educational culture, apart from that, ethnomathematics also preserves the existence of cultural values in the future. This research aims to describe the exploration of the decorative variety of Malay deli. In Malay Deli culture there are knick-knacks as Malay Deli decorations, such as tepak betel, balai, and pending. The results of this research showed that mathematical concepts were found in the Malay Deli Decorative Variety. This means that Tepak Sirih, Balai, and Pending can be used as teaching aids in mathematics learning. The mathematical concepts contained in this research are the concept of flat shapes and spatial shapes, namely trapezoids on tepak betel and balai, rectangles on tepak betel, balai, as well as pockets on the kekak musang shirt, circles on the circumference of the head for climbers, as well as the concept of prisms. with an isosceles trapezoid base on the betel palm.